Vitamin D Deficiency in Orthopedic Patients in Different Latitudes—First Study Comparing German and Greek Populations - Andreas Mamilos; Charalambos Matzaroglou; Gerrit S. Maier; Samer Zawy Alsofy; Philipp Drees; Konstantinos Kafchitsas (Osteology, 2023)
Vitamin D plays a pivotal role in calcium metabolism and bone mineralization. Sufficient vitamin D levels are important for the health and functionality of the musculoskeletal system. Hypovitaminosis D is a phenomenon affecting orthopedic patients worldwide. This study researched whether most orthopedic patients in two different cities of different countries had hypovitaminosis D, whether there was a correlation between sunshine hours and vitamin D serum levels, and whether hours of sunshine alone were enough to achieve vitamin D sufficiency among orthopedic patients regardless of their activities. The vitamin D serum levels of 500 orthopedic patients in Regensburg and 500 in Patras were assessed, in addition to their medical histories. The mean sunshine hours throughout the year were also calculated. Both the German and Greek groups showed hypovitaminosis D. Older patients were more affected. Although there were more hours of sunshine in Greece, Greek orthopedic patients also showed hypovitaminosis D. Hypovitaminosis D affects orthopedic patients independent of their latitude. Supplementation of vitamin D may be considered among orthopedic patients to achieve sufficient levels in serum. Sufficient vitamin D levels may be helpful for the treatment of orthopedic patients, reduce the negative effects of operations or postoperational settings.